2015
DOI: 10.1002/jaal.391
|View full text |Cite
|
Sign up to set email alerts
|

e‐Textbooks

Abstract: This article explores the digital reading preferences and strategies used by preservice teachers when reading an e‐textbook in a literacy methods course. The use of e‐textbooks is becoming more prevalent due to an increase in access to mobile devices, acceptance of e‐books in general, and the high cost of print textbooks. To ensure comprehension, teachers need an awareness of e‐textbook features and the processes for effectively reading text with embedded web links, video clips, and audio files. In this study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(35 citation statements)
references
References 34 publications
0
33
0
2
Order By: Relevance
“…Thus, instructor annotations may encourage students to annotate more. As Dobler (2015) claims, students' skill with enhanced features of etextbooks cannot be assumed based on appearances of being good at using digital devices and social networking tools. Ultimately, more research is needed to study the impact of instructor annotations on students' annotating behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, instructor annotations may encourage students to annotate more. As Dobler (2015) claims, students' skill with enhanced features of etextbooks cannot be assumed based on appearances of being good at using digital devices and social networking tools. Ultimately, more research is needed to study the impact of instructor annotations on students' annotating behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Students may be more likely to engage with and perceive as useful technologies with which they are already familiar; alternatively, they may have a strong preference for print-based texts based on prior experiences. A variety of factors are at play here: familiarity with and comfort levels of the medium or platform (Baek and Monaghan 2013;Chen et al 2014;Weisberg 2011), the cultural attitudes of learners (Kretzschmar et al 2013), the subject matter (John 2014), the length of text ( Students may declare their preference for print-based texts over e-texts, but they can also appreciate using a combination of the two (Dobler 2015;Falc 2013;Mizrachi 2015;Singer and Alexander 2016). While students overall appear to prefer printbooks, they are also satisfied with e-texts (Jeong 2012).…”
Section: The Importance Of Preference and Familiaritymentioning
confidence: 99%
“…While students overall appear to prefer printbooks, they are also satisfied with e-texts (Jeong 2012). Reasons for a preference for print-based texts can be the following: students may feel more easily distracted when reading e-texts (Dobler 2015); students perceive e-texts' page-to-page navigation tools as poor and the speed of page loading as slow (Muir and Hawes 2013); and students also encounter various technical difficulties when learning with e-texts, leading to frustration (Falc 2013). Print-based texts are also considered superior for studying large sections of text (Baek and Monaghan 2013).…”
Section: The Importance Of Preference and Familiaritymentioning
confidence: 99%
“…For example, Margolin, Driscoll, Toland, and Kegler's (2013) quantitative study of college students found no significant differences in the reading comprehension of students who read texts on paper, as PDFs, and with an e-reader. However, Dobler's (2015) qualitative study with equally skilled college-level readers had more mixed results, again highlighting the need for teachers to model effective strategies and acknowledge that students' personal experiences with reading influence their approaches to digital texts.…”
Section: Feature Articlementioning
confidence: 99%